Effects of different exercises on health-related physical fitness among middle-aged and elderly women - Bai, Xiaorong; Wang, Yuhui; Geok, Soh Kim; Jin, Zongqiang; Xiao, Wensheng; Zhang, Junlong (Frontiers in Psychology, 2025)
ObjectiveTo explore the effects of long-term exercise of Tai Chi Chuan, walking, and Jiamusi gymnastics on the health-related factors of physical fitness among middle-aged and elderly women.MethodsLong-term exercise Tai Chi Chuan group, walking group, Jiamusi gymnastics group, and non-exercise group were used to measure their health-related physical fitness, balance, and life satisfaction through long-term exercise Tai Chi Chuan group, walking group, Jiamusi gymnastics group, and non-exercise group matched by age, height, and weight.ResultsCompared with control group, Tai Chi Chuan were significant differences in all indicators, except systolic blood pressure (SBP), diastolic blood pressure (DBP), resting heart rate (RHR), and life satisfaction (p < 0.05). Walking were significant differences in RHR, force vital capacity (FVC), waist–hip ratio (WHR), sit and reach (SR), handgrip strength (HGS), and chair stand test (CS; p < 0.05). Jiamusi gymnastics had a significant difference in FVC, hip circumferences (HC), SR, HGS, and back scratch (BS). Compared with different exercise group, Tai Chi Chuan exercises significantly improved balance, SR, and WHR. Jiamusi gymnastics had a statistically significant impact on RHR. The CS was statistically impacted by walking.ConclusionMiddle-aged and older women are affected differently by different types of exercise. When the three groups—Tai Chi Chuan, walking, and Jiamusi gymnastics—were compared, it was discovered that Tai Chi Chuan had a greater impact on improving balance and trunk flexibility, Jiamusi gymnastics had a greater impact on improving cardiopulmonary fitness, and walking was more effective at strengthening the lower limbs.